2006
DOI: 10.1196/annals.1378.034
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity Signal Ensnarls Cell Adhesion, Cytoskeleton, and Matrix Proteins of Rat Osteoblasts

Abstract: Rat osteoblasts were cultured for 4 or 5 days aboard the Space Shuttle and solubilized during spaceflight. Post-flight analyses by quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) determined the relative mRNA levels of matrix proteins, adhesion molecules, and cytoskeletal proteins including osteopontin (OP), osteonectin (ON), CD44, alpha-tubulin, actin, vimentin, fibronectin (FN), and beta1-integrin. The mRNA levels of OP and alpha-tubulin in the flight cultures were decreased by 30% and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…Although there are complications to the use of these devices such as the potential for hypoxia [93], careful control of the bioreactor environment can lead to a stimulation of osteogenesis in rat calvarial osteoblasts [94] and in human palatal mesenchymal cells [95]. In contrast, growth of human mesenchymal stem cells under osteogenic conditions in a rotating cell culture system leads to disruption of actin stress fibers, decreased integrin signaling through FAK [96,97] and impaired osteoblastogenesis; these latter responses are consistent with the expectation that modeled microgravity exerts effects that are simply opposite to those of increased mechanical loading by hypergravity [98][99][100][101].…”
Section: Integrin-mediated Regulation Of Other Key Cell Functions In supporting
confidence: 79%
“…Although there are complications to the use of these devices such as the potential for hypoxia [93], careful control of the bioreactor environment can lead to a stimulation of osteogenesis in rat calvarial osteoblasts [94] and in human palatal mesenchymal cells [95]. In contrast, growth of human mesenchymal stem cells under osteogenic conditions in a rotating cell culture system leads to disruption of actin stress fibers, decreased integrin signaling through FAK [96,97] and impaired osteoblastogenesis; these latter responses are consistent with the expectation that modeled microgravity exerts effects that are simply opposite to those of increased mechanical loading by hypergravity [98][99][100][101].…”
Section: Integrin-mediated Regulation Of Other Key Cell Functions In supporting
confidence: 79%
“…Acridine orange/ethidium bromide staining and Hoechst 33342 staining revealed no increase in apoptosis or necrosis after 31 parabolas. In contrast, Kumei et al [36] reported a decrease in OPN gene expression, but they also found an increase in fibronectin gene expression in rat osteoblasts when cultured for a longer period of 4 or 5 days aboard the Space Shuttle [36]. The mRNA levels of actin, vimentin, or 1 -integrin (ITGB1) did not change under space flight conditions.…”
Section: Short-term Microgravity Alters Gene Expression Of Extracellumentioning
confidence: 82%
“…Cytoskeletal changes occur in a variety of cell types including lymphocytes [35], thyrocytes [3], glial cells [33], chondrocytes [6], endothelial cells [4] and osteoblasts [36,37] during real microgravity and various simulation approaches. The external signals (altered gravity conditions) might be transduced into intracellular signals through the extracellular matrix, adhesion molecules, and the cytoskeletal structure.…”
Section: Short-term Microgravity Alters the Distribution And Amount Omentioning
confidence: 99%
“…These physical phenomena can influence cell shape, metabolism, movement, and exocrine and signal conduction, either directly or indirectly (Freed and Vunjak-Novakovic, 2002). Previous studies have suggested that cytoskeleton and membrane structural changes occur when cells are subjected to weightlessness (Ingber, 1999;Infanger et al, 2004Infanger et al, , 2006aKumei et al, 2006). A corresponding redistribution of the cell structure occurs to maintain balance.…”
Section: A B Discussionmentioning
confidence: 99%